2017
DOI: 10.1016/j.jcf.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The 1-min sit-to-stand test in cystic fibrosis — Insights into cardiorespiratory responses

Abstract: The 1-min STS test elicits a substantial but lower cardiorespiratory response compared to a maximal cycle ergometry CPET. While Power and STS repetitions are both valid outcome measures of functional capacity, STS repetitions are clinically more practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
1
34
2
3
Order By: Relevance
“…9 In contrast, continuous S pO 2 measurements during the 1-min STS are hampered by movement artifacts, 13 and our group has re- cently shown that the lowest S pO 2 often occurs during the first minute after the sit-to-stand exercise. 3,13 To our knowledge, no previous study has investigated the prognostic value of oxygen desaturation during the 1-min STS, as previously reported for the 6MWT. 28 In our study, the 1-min STS and the 6MWT showed similar correlations with knee extensor strength.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…9 In contrast, continuous S pO 2 measurements during the 1-min STS are hampered by movement artifacts, 13 and our group has re- cently shown that the lowest S pO 2 often occurs during the first minute after the sit-to-stand exercise. 3,13 To our knowledge, no previous study has investigated the prognostic value of oxygen desaturation during the 1-min STS, as previously reported for the 6MWT. 28 In our study, the 1-min STS and the 6MWT showed similar correlations with knee extensor strength.…”
Section: Discussionmentioning
confidence: 73%
“…The subjects were instructed to stand up and sit down as often as possible at a selfchosen speed for 1 min, and the number of sit-to-stand repetitions was counted. Verbal encouragement was not provided during the test, but subjects were informed when 15 s were left until the test terminated at 60 s. 3,4,13,14 Subjects were allowed to stop at any time during the test. A repetition was defined as the legs being completely straight at the end of the stand-up phase, and the bottom had to have clear contact with the chair when sitting down.…”
Section: Measurementsmentioning
confidence: 99%
“…The 1-minute sit-to-stand test (1MSTS) was performed using a standardized protocol [17][18][19] on a conventional chair without armrest and a seat height of 46 cm. For safety reasons, the chair was positioned against a wall.…”
Section: Functional Exercise Capacitymentioning
confidence: 99%
“…32 Dyspnoea scores on 1minSTS did not differ from the 30secSTS but were significantly greater than 5STS (median 2.5 vs 1 vs 0) with a similar pattern of findings for systolic blood pressure (median 30 vs 20 vs 0 mmHg). 32 In comparison to the 6MWT and cardiopulmonary exercise test (CPET), the 1minSTS provoked less oxyhaemoglobin desaturation and a smaller rise in heart rate ( Table 3) 37 Symptom scores for dyspnoea and fatigue were variable, with some studies reporting that they were similar across the tests, 25,39 higher on CPET than 1minSTS, 37 higher on 6MWT than 1 minSTS, 35 or higher on 1minSTS than 6MWT. 16 Exercise prescription: No studies used any of the STS tests for exercise prescription.…”
mentioning
confidence: 99%